Healthcare Workers’ Knowledge, Practices, and Involvement in Hospital Waste Management in Rupandehi, Nepal - Adhikari, Chham Bahadur; Roy, Monalisa; Adhikari, Krishna; Adhikari, Hom Prasad; Raman, Ramendra; Timilsena, Dikshya (Journal of Neonatal Surgery, 2025)
Healthcare waste management remains a major challenge in low and middle-income countries, where rapid urbanization, limited infrastructure, and weak enforcement hinder safe disposal practices. This study assessed knowledge, practices, and involvement of healthcare workers in hospital waste management at Rupandehi District Hospital, Nepal. A cross-sectional design was used, with data collected from 60 healthcare workers who were likely exposed to healthcare waste through a structured questionnaire covering knowledge, practices, and involvement. Descriptive and statistical analyses were performed to interpret the responses. The results showed that healthcare workers had a high level of knowledge, with a mean score of 4.67 out of 5 (93.4% accuracy). However, the practice score was somewhat lower at 4.05 out of 5 (81%), while involvement was the weakest area, with a mean score of 8.62 out of 14 (61.6%). This gap highlights a persistent disconnect between knowledge and its consistent application in daily hospital activities. The study emphasizes the urgent need for targeted interventions such as ongoing refresher training, providing protective gear, implementing monitoring systems, and establishing supportive policies to enhance HCWs’ active participation in HCWM. These measures are vital to reduce occupational hazards, limit community exposure, and protect environmental health.